Factors related to adherence to stay at the isolation house and health protocols for COVID-19 confirmed positive people in Denpasar, Bali, Indonesia - Ni Nyoman Sudarti; Widarini, Ni Putu; Ni Ketut Sutiari (Public Health and Preventive Medicine Archive, 2023)
Background and purpose: Quarantine in the isolation house for people who are confirmed having COVID-19 is essential to reduce transmission in the community. This research aimed at determining factors associated with compliance to isolation for 14 days and the implementation of health protocols for people who are confirmed positive for COVID-19. Methods: This study applied analytic cross-sectional design, which was conducted in the working area of the Public Health Centre (PHC) II North Denpasar. The samples were 279 people whom selected by simple random sampling. The collected data included sociodemographic characteristics, adherence to stay in the isolation houses and to apply health protocols, perceptions to compliance, cues to action, self-efficacy, knowledge, and social support. The data were analysed by Stata including descriptive analysis, followed by Chi-square Test and Multiple Logistic Regression. Results:  As high as 60.6% of respondents complied to stay for 14 days in the isolation house and implemented health protocols. From multivariable analysis, the higher likelihood to comply with staying at the isolation houses for 14 days and applying health protocols were among female (AOR=3.02; 95%CI: 1.54-5.90, having higher education (AOR=6.03; 95%CI: 3.09-11,77), those having high self-efficacy (AOR=3.43; 95%CI: 1.81-6.50), and those having good knowledge (AOR=2.18; 95%CI: 1.19-3.98). Conclusion: About a third of the respondents did not comply with isolation for 14 days in the isolation house nor apply etiquette according to the health protocols, thus indicating a high risk of transmitting COVID-19 to others. It is necessary to promote health targeting people with low knowledge level and to provide social support from family, surrounding community and government.